Formation de la pensée Janus du physicien-poète Gaston Bachelard : lien entre l’approche psychanalytique et l’approche phénoménologique à travers l’étude des images matérielles - Ben Nila, Hedia (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
The Bachelardian work is a plural work, it is divided between two universes commonly considered as antagonistic and hostile: the universe of science on the one hand and the universe of poetry on the other. But her reflections on the material imagination seem to be first scientific and then fed by literary imprints. In this work we are interested in understanding the formation of this Janus thought, which is referred to by some as a modest philosophy. We seek to explore the different approaches with which he studied material images ton found the link that is woven between them. In the finality to detect, that the Bachelardian poetics that at the beginning was scaffolded on a psychoanalytical approach inspired by his epistemological works, changes of orientation towards a phenomenological approach in the need of an ontology to found itself. Keywords: Material Images, Janus Thought, Psychoanalytical Approach, Phenomenological Approach, Poetic Imagination